Legal Inconsistency on the Right to Build: Investment, Agrarian Rights, and Constitution - Lego Karjoko; Jaelani, Abdul Kadir; Ravi Danendra (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
The legal duration of the Right to Build (Hak Guna Bangunan) in the new capital city has raised concerns due to inconsistencies across regulatory frameworks. Current policies suggest that HGB may be granted for up to 160 years in two cycles, creating potential conflict with previous legal norms that provide for shorter durations. This study aims to assess the legal validity of the extended tenure of HGB within the context of national land law and to propose a justice-oriented regulatory model. The research adopts a normative legal method, utilizing primary and secondary legal materials, with a statutory and conceptual approach. The findings of this study are twofold: First, the regulation concerning HGB in the new capital lacks legal validity based on Lon L. Fuller’s theory of legal systems, as it contains ambiguous provisions, contradicts existing laws, and undermines legal certainty due to the possibility of frequent changes. Second, a just regulatory model should be grounded in the broader public interest and aligned with the moral and philosophical foundations of the national ideology, particularly the principle of social justice, to ensure equitable land access and promote sustainable capital development.